Initial experience with CDK4/6 inhibitor-based therapies compared to antihormone monotherapies in routine clinical use in patients with hormone receptor positive, HER2 negative breast cancer — Data from the PRAEGNANT research network for the first 2 years of drug availability in Germany. (December 2020) - Schneeweiss, Andreas; Ettl, Johannes; Lüftner, Diana; Beckmann, Matthias W.; Belleville, Erik; Fasching, Peter A.; Fehm, Tanja N.; Geberth, Matthias; Häberle, Lothar; Hadji, Peyman; Hartkopf, Andreas D.; Hielscher, Carsten; et al.
Abstract: Purpose: Treatment with CDK4/6 inhibitors and endocrine therapy (CDK4/6i + ET) is a standard for patients with advanced hormone receptor–positive, HER2-negative (HR + HER2–) breast cancer (BC). However, real-world data on the implementation of therapy usage, efficacy, and toxicity have not yet been reported. Methods: The PRAEGNANT registry was used to identify advanced HR + HER2– BC patients (n = 1136). The use of chemotherapy, ET, everolimus + ET, and CDK4/6i + ET was analyzed for first-line, second-line, and third-line therapy. Progression-free survival (PFS) and overall survival (OS) were also compared between patients treated with CDK4/6i + ET and ET monotherapy. Also toxicity was assessed. Results: CDK4/6i + ET use increased from 38.5% to 62.7% in the first 2 years after CDK4/6i treatment became available (November 2016). Chemotherapy and ET monotherapy use decreased from 2015 to 2018 from 42.2% to 27.2% and from 53% to 9.5%, respectively. In this early analysis no statistically significant differences were found comparing CDK4/6i + ET and ET monotherapy patients with regard to PFS and OS. Leukopenia was was seen in 11.3% of patients under CDK4/6i + ET and 0.5% under ET monotherapy. Conclusions: In clinical practice, CDK4/6i + ET has been rapidly implemented. A group of patients with a more unfavorable prognosis was possibly treated in the real-world setting than in the reported randomized clinical trials. The available data suggest that longer follow-up times and a larger sample size are required in order to identify differences in survival outcomes. Studies should be supported that investigate whether chemotherapy can be avoided or delayed in this patient population by using CDK4/6i + ET. Highlights: CDK4/6i + ET use increased from 39% to 63% after becoming available. Chemotherapy and ET monotherapy use decreased from 42% to 27% and 53%–10%. There was no difference between CDK4/6i + ET and ET monotherapy regarding PFS and OS.